The Impacts of Distributive Justice and Perceived Organizational Support on Turnover Intention within The Poultry Industry - Sherly Rosalina Tanoto; Merry Yuanita Sugiharto (Petra International Journal of Business Studies, 2018)
Increased numbers of job-hopping in Indonesia might result in negative costs for organizations. Earlier research in turnover intention tends to emphasize organizational commitment yet it neglects the importance of perceived fairness in allocating results and perceived support from organizations. The aim of this study is to investigate the influence of distributive justice and perceived organizational support to turnover intention in a company within the poultry industry. This study implements quantitative method by administering surveys to 142 fulltime employees. Partial Least Square was utilized to test the research model. Results of this study demonstrated that perceived organizational support is the most significant factor for turnover intention and distributive justice has higher influence on perceived organizational support compared with turnover intention. These findings contribute to the development of employers and managers’ initiatives to promote support and distributive fairness toward their employees.